Lung X-ray Changes in Premature Neonates with Respiratory Failure - S. A. Perepelitsa; A. M. Golubev; V. V. Moroz (Общая реаниматология)
Objective: to study lung X-ray changes in premature neonates born from multiple pregnancy respiratory failure. Subjects and methods. Forty-six premature neonates born from multiple pregnancy who had RF were followed up; of them 9 (39.1%) and 14 (60.9%) were monochorial-diamniotic and diochorial-diamniotic twins, respectively. Lung X-ray films were analyzed in 39 infants with RF. By taking into account the babies’ gestational age and the clinical picture of RF, the newborn infants were given the exogenous surfactant Curosurf. Clinical evaluation of their status and plain lung X-ray films were made. If a fatal outcome occurred, the lung was investigated morphologically. Results. There were different lung X-ray patterns: no abnormal changes; the following X-ray signs were most characteristic: a less clear lung field transparency and an increased lung pattern in the middle internal areas of both lungs; a false aspiration pneumonia pattern caused by the Curosurf remnants being present in the airways; hyaline membrane disease and congenital pneumonia were detected in 5.1% of cases. Atelectases were found with the late administration of Curosurf. Conclusion. The prophylactic administration of Curosurf causes lung X-ray changes in the premature neonates with RF. Abnormal lung changes were absent most frequently in the first 24 hours of mechanical ventilation (MV). Atelectases and intrapulmonary hemodynamic disorders were found with the later, the so-called medical Curosurf administration. The emergence of new treatments for RF, such as early transition to MV and administration of exogenous surfactants, in premature neonates alters not only the clinical, but also X-ray pattern of respiratory distress syndrome. Key words: respiratory failure, atelectases, respiratory distress syndrome, premature neonates, multiple pregnancy, lung X-ray film.